Class II Cytochrome P450 Reductase Governs the Biosynthesis of Alkaloids - Parage, Claire (Plant Physiol, 2016)
Expansion of the biosynthesis of plant specialized metabolites notably results from the massive recruitment of cytochrome P450s that catalyze multiple types of conversion of biosynthetic intermediates. For catalysis, P450s require a two-electron transfer catalyzed by shared cytochrome P450 oxidoreductases (CPRs), making these auxiliary proteins an essential component of specialized metabolism. CPR isoforms usually group into two distinct classes with different proposed roles, namely involvement in primary and basal specialized metabolisms for class I and inducible specialized metabolism for class II. By studying the role of CPRs in the biosynthesis of monoterpene indole alkaloids, we provide compelling evidence of an operational specialization of CPR isoforms in Catharanthus roseus (Madagascar periwinkle). Global analyses of gene expression correlation combined with transcript localization in specific leaf tissues and gene-silencing experiments of both classes of CPR all point to the strict requirement of class II CPRs for monoterpene indole alkaloid biosynthesis with a minimal or null role of class I. Direct assays of interaction and reduction of P450s in vitro, however, showed that both classes of CPR performed equally well. Such high specialization of class II CPRs in planta highlights the evolutionary strategy that ensures an efficient reduction of P450s in specialized metabolism.